Corrigendum to “Phenotypic, genotypic, and resistome of mesophilic spore-forming bacteria isolated from pasteurized liquid whole egg” [Food Res. Inter. 184 (2024) 114215] - Alexandra A.I.A. Chincha; Héctor D.S. Canales; Marina P. Marone; Arthur K.R. Pia; Luisa Freire; Dionisio P. Amorim-Neto; Marcelo F. Carazzolle; Anderson S. Sant’Ana (Food Research International, 2024)

Phenotypic, genotypic, and resistome of mesophilic spore-forming bacteria isolated from pasteurized liquid whole egg - Alexandra A.I.A. Chincha; Marina P. Marone; Arthur K.R. Pia; Luisa Freire; Dionisio P. Amorim-Neto; Marcelo F. Carazzolle; Anderson S. Sant'Ana (Food Research International, 2024)

Carbapenem-resistant Enterobacteriaceae among kidney transplant recipients – insights on the risk of acquisition and CRE infection - Maristela P. Freire; Laina B. Carvalho; Jose Otto Reusing; Fernanda Spadão; Max Igor B. F. Lopes; William C. Nahas; Elias David-Neto; Ligia C. Pierrotti (Infectious Diseases, 2021)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The role of therapy with aminoglycoside in the outcomes of kidney transplant recipients infected with polymyxin- and carbapenem-resistant Enterobacteriaceae - Maristela P. Freire; Doroti de Oliveira Garcia; Ana Paula Cury; Gabriela R. Francisco; Nathamy F. dos Santos; Fernanda Spadão; Maria Fernanda Campagnari Bueno; Carlos Henrique Camargo; Flavio J. de Paula; Flavia Rossi; Willian C. Nahas; Elias David-Neto; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Levels of oxidative stress markers: correlation with hepatic function and worm burden patients with schistosomiasis - G. Cunha; V. Silva; K. Bessa; M. Bitencourt; U. Macêdo; F. Freire-Neto; R. Martins; C. Assis; T. Lemos; M. Almeida; A. Freire (Acta Parasitologica, 2012)
Schistosomiasis is caused by Schistosoma mansoni and is a public health problem in Brazil. The typical granulomatous lesion is associated with the increase in the oxidative damage by generation of free radicals. The aim of this work was to correlate some oxidative stress markers with the worm burden on carriers of schistosomiasis (n = 30) in the acute phase in comparison to healthy subjects (n = 30). The pro-oxidant parameter used was the colorimetric quantification of reactive substances to thiobarbituric acid, while the antioxidant markers used were blood content of reduced glutathione and determination of the activity of catalase. The worm burden was assessed by Kato-Katz method. The results pointed out that initially there was no difference in the catalase activity. However, there was a positive correlation between the increase in parasitic load and intensity of lipid peroxidation, and decrease in the content of reduced glutathione. Additionally, only the aspartate aminotransferase levels presented to be high, while there was a decrease in bilirubin level. Therefore, a possible association between the establishment of the oxidative stress in tissue and the parasitic load of Schistosoma mansoni is suggested.